Replacement names and nomenclatural comments for problematic species-group names in Europe’s Neogene freshwater Gastropoda - Neubauer, Thomas A.; Harzhauser, Mathias; Georgopoulou, Elisavet; Mandic, Oleg; Kroh, Andreas (Zootaxa, 2014)
Over the last 250 years of taxonomic descriptions of freshwater gastropods a large number of primary and secondary homonyms were produced. Several of them have now been uncovered in the course of a new database project. To overcome the associated nomenclatural problems we propose 10 replacement names: Theodoxus pseudodacicus nom. nov., Theodoxus stoicai nom. nov., Viviparus deleeuwi nom. nov., Viviparus lubenescuae nom. nov., Viviparus wesselinghi nom. nov., Melanopsis anistratenkoi nom. nov., Melanopsis gearyae nom. nov., Melanopsis magyari nom. nov., Melanopsis vrcinensis nom. nov., and Pyrgula rusti nom. nov. Additionally, we discuss taxa that might become secondary homonyms because of uncertain genus attributions. The genera Melanoptychia Neumayr, 1880 and Boistelia Cossmann, 1909 are synonymized with Melanopsis Férussac, 1807 in Férussac & Férussac, 1807 based on the lack of sufficient separation criteria. Involved combinations are expounded and recombined accordingly. The nomenclatural problems regarding Melanopsis costata Fuchs, 1870 (non Olivier, 1804) and Planorbis varians Fuchs, 1870 sensu Bandel (2010) are discussed.